Intertropical convergence zone and El Niño Southern oscillation controls on late Holocene rainfall variability in Palau - Jalene Nalbant; Larissa Schneider; Carol V. Tadros; Geoffrey Clark; Susan Rule; Georgia L. Stannard; Sabika Maizma; Matthew Wolhowe; Julian P. Sachs; Stewart Fallon; Simon G. Haberle (Journal of Paleolimnology, 2026)
The Tropical West Pacific is an understudied region in environmental and archaeological studies when compared to continental regions. The unique geologies, climate systems, and ecological dynamics in the Tropical West Pacific greatly limit the transferrability of palaeoenvironmental proxies established from studies outside of this region. To address this gap, we present a ~5600 yr multi-proxy record of environmental change from a marine lake in Belau (Palau in English). The Belau archipelago is located in the Tropical West Pacific, a region with links to global atmospheric, oceanic, and hydrological climate systems. Additionally, this archipelago is central to debates of early human mobility in the Tropical Pacific ~3500 to 3000 years ago. By combining high-resolution data (XRF) with low-resolution proxies (pollen, fern spore, charcoal, TOC, δ 13 C, TN, δ 15 N, TOC:TN) we are able to reconstruct the response of a coastal Belauan system to changing Holocene climate dynamics and identify the primary processes driving these changes. Two distinct climate signatures are identified in the multi-proxy record. Drier and warmer conditions during Phase I (~ 5600 to 3250 cal yr BP, 689–400 cm) are consistent with local records of a southern displacement of the Intertropical Convergence Zone (ITCZ) and regional records of long-term cooling trends in the Northern Hemisphere. Phase II (~ 3250 to − 63 cal yr BP) marks a transition to wetter and cooler conditions in Belau, associated with the northward migration of the ITCZ and intensification of El Niño Southern Oscillation (ENSO). The Phase II transition coincides with a shift in catchment vegetation, as mangroves retreat and the rainforest expands, and evidence of rising local sea level. A brief vegetation disturbance event ~1250 to 500 cal yr BP does not align with documented changes in regional climate systems, suggesting that this was a localised signature. Currently it is unclear if an enrichment in bulk sediment δ 15 N values at ~1250 cal yr BP was driven by rising sea levels or local ecological dynamics and future studies should seek to clairfy the drivers of this signal.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Late Quaternary hydroclimate variability in Madagascar and its connection to atmospheric circulation patterns - Christos Katrantsiotis; Simon Haberle; Anneli Ekblom; Rienk H. Smittenberg; Jan Risberg; Susan Rule; Geoff Clark; Atholl Anderson; Amy Prendergast; Aaron Carmens; Chantal Radimilahy; Lucien Rakotozafy; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)